DXA: Technical aspects and application. Issue 8 (August 2016) - Bazzocchi, Alberto; Ponti, Federico; Albisinni, Ugo; Battista, Giuseppe; Guglielmi, Giuseppe
Highlights: The purposes of this Special Issue are: To appreciate the role of DXA in the study of body composition. To understand potential limitations and pitfalls of DXA in the analysis of body composition. To learn about technical elements and methods, and to become familiar with biomarkers in DXA. Abstract: The key role of dual-energy X-ray absorptiometry (DXA) in the management of metabolic bone diseases is well known. The role of DXA in the study of body composition and in the clinical evaluation of disorders which directly or indirectly involve the whole metabolism as they may induce changes in body mass and fat percentage is less known or less understood. DXA has a range of clinical applications in this field, from assessing associations between adipose or lean mass and the risk of disease to understanding and measuring the effects of pathophysiological processes or therapeutic interventions, in both adult and paediatric human populations as well as in pre-clinical settings. DXA analyses body composition at the molecular level that is basically translated into a clinical model made up of fat mass, non-bone lean mass, and bone mineral content. DXA allows total and regional assessment of the three above-mentioned compartments, usually by a whole-body scan. Since body composition is a hot topic today, manufacturers have steered the development of DXA technology and methodology towards this. New DXA machines have been designed to accommodate heavier and larger patients and to scan wider areas. New strategies, such as half-body assessment, permit accurate body scan and analysis of individuals exceeding scan field limits. Although DXA is a projective imaging technique, new solutions have recently allowed the differential estimate of subcutaneous and intra-abdominal visceral fat. The transition to narrow fan-beam densitometers has led to faster scan times and better resolution; however, inter- or intra-device variation exists depending on several factors. The purposes of this review are: (1) to appreciate the role of DXA in the study of body composition; (2) to understand potential limitations and pitfalls of DXA in the analysis of body composition; (3) to learn about technical elements and methods, and to become familiar with biomarkers in DXA.